Identity, Identity Politics, and Neoliberalism - Wrenn, Mary (Panoeconomicus, 2014)
With the intensification of neoliberalism, it is useful to examine how some individuals might cope with the irrationality of the system. Neoliberalism cloaks the execution of the corporate agenda behind rhetorical manipulation that advocates for limited government. The corollary absence of government involvement on behalf of the citizenry writ large disarms the means of social redress for the individual. Democracy funded and fueled by corporate power thereby disenfranchises the individual, provoking some to search for empowerment through identity politics. The argument set forth suggests that individuals construct, reinforce, or escalate allegiance to identities as a coping mechanism, some of which manifest in violent identity politics. Key words: Identity, Identity politics, Neoliberalism, Heterodox economics, Agency. JEL: B50, B52, N32.